Traditional Game-Based Learning Model In Early Childhood Education: A Case Study at TKIT Al-Hikmah - Susanto, Dwi; Pusporini, Widowati; Lestari, Titi (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, 2022)
This study aims to describe the implementation of a traditional children's game-based learning model to train visual-spatial intelligence of kindergarten students. A descriptive qualitative method was employed to describe systematic, factual, and accurate facts, properties, and the relationship between the phenomena studied. This study also uses holistic reflection methods through the meaning of learning games for children which can promote their visual-spatial abilities. The students of TKIT Al-Hikmah Secang, Magelang were involved as the research subjects. The results indicate that traditional games can train children’s visual-spatial intelligence and such games can be revived. The applied learning model offers moral and social education and is strongly suggested to be implemented in early education to strengthen visual-spatial intelligence and the other multiple intelligences.